THE INFLUENCE OF WORK MOTIVATION, WORK ENVIRONMENT, AND COMPENSATION ON STAFF WORK ETHIC AT PT VOKSEL ELECTRIC TBK CILEUNGSI - SAMUEL, ANDREAS; PURBASARI, NIKEN; WIDAYATI, NURTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aim of this research is to determine what variables can influence work ethic. Some of the variables that will be studied are Work Motivation, Work Environment, and Compensation. To test the hypothesis, this research uses descriptive and causality techniques along with multiple regression. This research involved 81 employees of PT Voksel Electic Tbk Cileungsi at staff level. The data for this research comes from primary data distributed to employees via a Likert Scale questionnaire. Convenience sampling is used. The empirical results of the research show that the work ethic at PT Voksel Electic Tbk is influenced by work motivation, while the work environment and compensation have no effect on work ethic.